Voix d’islam, résonances viatiques : Perception de la prière musulmane chez quelques voyageurs en Orient au xixe siècle - Sarga Moussa (Viatica)
Considered for a long time as tales of seeing, the journeys of writers to the Orient also bear witness to an auditory apprehension of the world. The description and perception of Muslim prayer in 19th-century travel literature are convincing examples given that hearing has an important place in the narration. Whether sensitive to, or even disturbed or seduced by the auditory experience of the Orient, travel writers open up a space for anthropological possibilities.